Sport event hosting and provincial economic growth: Evidence from the Bangsaen21 Half Marathon in Thailand - Thanavutd Chutiphongdech; Peera Tangtammaruk; Aritat Aksorntap; Samkhumpha Tovara; Supaporn Daengmeesee; Nattapon Siwareepan (Humanities & Social Sciences Communications)
Abstract This research article investigates provincial economic growth through sport event hosting, using the Bangsaen21 Half Marathon (B21) in Chonburi Province, Thailand, as a case study. An explanatory sequential mixed-method approach was employed to examine the long-term impacts of the event on the local economy. Using time-series econometric techniques, the first-stage quantitative analysis revealed a significant impact of the event on provincial-level tourism revenue. The second-stage qualitative analysis, employing descriptive and reflexive thematic analysis of open-ended questionnaire surveys, further supported these findings by examining the spending behaviours of B21 participants. The analysis revealed that nearly all B21 runners spent on accommodation, food and drink, and retail products, positioning the event as a local economic stimulant. This research contributes to the literature on sport event impact assessment by offering methodological insights and exploring an under-studied contextual setting, particularly regarding micro-level economic impacts. The study concludes with several policy implications for local economic development and outlines future research directions for scholars in this field.